A Stepwise Guide to Freehand Bending of Orbital Floor Mesh. Issue 3 (March 2022) - Rajendiran, Saravanan; Krishnan, B.
Abstract : Summary: Orbital fractures can often result in enophthalmos or diplopia. Orbital reconstruction with titanium meshes is the current treatment modality. Adapting the titanium orbital floor mesh is often challenging due to the complex anatomy of the orbital floor. Here, a stepwise free hand bending technique of a titanium orbital floor mesh is described. The bending can be done preoperatively, and mesh fit can be checked against a dry anatomical skull before sterilization. The methodical approach to free hand bending of titanium orbital floor mesh minimizes the intraoperative adjustments and permits quick orbital reconstruction. Trainees and less-experienced surgeons can benefit from the methodical approach to free hand bending of titanium orbital floor mesh.